2004
DOI: 10.1007/s00442-004-1509-3
|View full text |Cite
|
Sign up to set email alerts
|

Disturbance of freshwater habitats by anadromous salmon in Alaska

Abstract: High densities of habitat modifiers can dramatically alter the structure of ecosystems. Whereas spawning sockeye salmon ( Oncorhynchus nerka) dig nests that cover over 2 m(2) and are at least 20 cm deep, and can spawn at high densities, relatively little attention has been devoted to investigating the impacts of this disturbance. We hypothesized that this temporally and spatially predictable bioturbation has large impacts on the coastal aquatic habitats used by sockeye. We experimentally investigated the impac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
98
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(102 citation statements)
references
References 52 publications
4
98
0
Order By: Relevance
“…We found that streams with elevated salmon densities had fewer invertebrates in the spring and fall and that invertebrate biomass was higher upstream of salmon spawning barriers compared to downstream, regardless of season. These findings support the disturbance effect (Moore et al 2004), whereby invertebrate biomass downstream of the barriers might not have had time to recover from spawning the previous fall. Moore and Schindler (2008) found that invertebrate dry mass did not fully recover shortly after spawning but returned to near normal levels the following year prior to spawning.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…We found that streams with elevated salmon densities had fewer invertebrates in the spring and fall and that invertebrate biomass was higher upstream of salmon spawning barriers compared to downstream, regardless of season. These findings support the disturbance effect (Moore et al 2004), whereby invertebrate biomass downstream of the barriers might not have had time to recover from spawning the previous fall. Moore and Schindler (2008) found that invertebrate dry mass did not fully recover shortly after spawning but returned to near normal levels the following year prior to spawning.…”
Section: Discussionsupporting
confidence: 75%
“…This scenario would also explain the negative correlation of invertebrate biomass density with algae and biofilm; depressed invertebrate grazer populations could release algae in the biofilm from grazing pressure . In combination or isolation, a salmon subsidy, benthic disturbance with slow invertebrate recovery or a trophic cascade could explain the decline in spring invertebrate biomass density, while substrate disturbance during spawning, as shown by others, would explain the decline observed in the fall (Moore et al 2004, Holtgrieve and Schindler 2011.…”
Section: Discussionmentioning
confidence: 83%
See 2 more Smart Citations
“…have been found to modify significantly instream hydraulic conditions, reducing flow velocity within individual stands and leading to fine sediment deposition of up to 0.085 m 3 m -2 in a single month (Wharton et al, 2006). The creation of spawning redds by salmonid fish removes fine sediment from the surface layers of the substrate, changing the local bed material grain-size distribution (Kondolf et al, 1993;Moore et al, 2004) and, at popular spawning sites, redd construction can substantially affect vertical sediment sorting, armour development and bedload flux (Gottesfeld et al, 2004). The foraging activities of other fish species may have significant cumulative impacts on the presence of macrophyte and local substratum composition (Power, 1990;Flecker, 1996;Statzner et al, 2003b).…”
Section: Introductionmentioning
confidence: 99%